At Odds Over INCO: The International Nickel Company of Canada and New Caledonian Politics in the 1960s - Gendron, Robin (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2009)
In the 1960s, the International Nickel Company of Canada (INCO) sought to preserve its dominance of the global nickel industry by securing access to New Caledonia’s abundant reserves of nickel ore. In attempting to do so, however, INCO became embroiled in an acrimonious political dispute between New Caledonian autonomists, who wanted to diversify the territory’s economic activities and secure greater self-government from French rule, and the government of France, which considered INCO a threat to French sovereignty over New Caledonia and France’s interests in the Pacific. In obstructing INCO’s ability to operate in New Caledonia throughout the 1960s, however, the French government inadvertently galvanized the territory’s nationalists and increased their demands for autonomy from France.